Optimalisasi Keseimbangan Lintasan Dengan Penerapan Large Candidate Rule dan Regional Approach Pada Usaha Perabot - Wahyudi, Dirza Ilham; Meldia Fitri; Yetrina, Mutiara (Sekolah Tinggi Teknologi Dumai, 2024)
Difa Perabot is a small industry engaged in furniture manufacturing, producing cabinets, sofas, and doors. This research aims to optimize the production line balance in the cabinet manufacturing process. The methods used are the Large Candidate Rule and the Regional Approach. Before optimization, the line efficiency was recorded at 47.23%, with a Balance Delay of 52.77% and a Smoothness Index of 21, involving 6 workstations. After applying the Large Candidate Rule, the efficiency increased to 79.60%, while the Balance Delay decreased to 20.40%. Idle Time was recorded at 98.99 minutes, with a Smoothness Index of 10, and the number of workstations reduced to 4. The Regional Approach showed the same line efficiency of 79.60%, a Balance Delay decrease to 20.40%, and Idle Time of 99.00 minutes, with a Smoothness Index remaining at 10 and 4 workstations. The research results indicate that the Large Candidate Rule method is more effective, reducing the number of workstations to 4 and significantly improving line efficiency while decreasing Balance Delay and Smoothness Index.